Personalized feedback improves cardiovascular risk perception and physical activity levels in persons with HIV: results of a pilot randomized clinical trial. Issue 6 (3rd June 2021) - Cioe, Patricia A.; Merrill, Jennifer E.; Gordon, Rebecca E.F.; Guthrie, Kate M.; Freiberg, Matthew; Williams, David M.; Risica, Patricia Markham; Kahler, Christopher W.
ABSTRACT: People with HIV (PWH) have an elevated risk for cardiovascular disease (CVD) compared with the general population. This study examined the feasibility, acceptability and preliminary efficacy of a tailored intervention aimed at increasing CVD risk perception and the adoption of heart-healthy behaviors in PWH. Forty adults were randomized to receive personalized feedback on CVD risk and discussion of risk reduction or health education. Participants were issued pedometers and seen for two treatment sessions. Participants were 60% male and had a mean age of 51.5 years. Ninety percent of participants completed all study sessions indicating good feasibility and acceptability. A medium effect size for the difference between treatment and control groups was found on both the Perceived Risk for Heart Disease ( d = .38) and the Rapid Eating and Activity for Patients scales ( d = .56) at 12 weeks. Atherosclerotic cardiovascular disease (ASCVD) risk score moderated the effect of treatment, such that at high (but not low) ASCVD risk, active intervention, compared to control, was associated with a greater increase in steps between baseline and both 8 ( d = .38) and 12 weeks ( d = .55). Findings provide preliminary evidence that tailored interventions delivered by nurses may be effective for primary prevention of CVD in PWH.